How to sell to retail : the secrets of getting your product to market - Rayner, Clare (Kogan Page, 2013)
"For people with a product to sell, there's only so much growth that can be sustained by selling directly to end users. The ultimate key to really developing a business into a bigger enterprise is to get it sold by retailers. However, retailers are cautious about who they do business with - they don't like to take risks, so it's important to give a great outward impression. Working through this series of 5 logical sections, broken down into 12 steps, How to Sell to Retail will explain how to look big, plan big, pitch big, get big and stay big though successfully selling to retailers"--Resumé vydavatele
Obsahuje rejstřík
Keywords: maloobchod; marketing; prodej; retail trade; selling; příručky; případové studie; handbooks, manuals, etc; case studies